2013
DOI: 10.1177/0956462412473890
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal association of venue stability with consistent condom use among female sex workers in two Mexico–USA border cities

Abstract: Summary We examined the relationship between venue stability and consistent condom use (CCU) among female sex workers who inject drugs (FSW-IDUs; n = 584) and were enrolled in a behavioural intervention in two Mexico–USA border cities. Using a generalized estimating equation approach stratified by client type and city, we found venue stability affected CCU. In Tijuana, operating primarily indoors was significantly associated with a four-fold increase in the odds of CCU among regular clients (odds ratio [OR]: 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 54 publications
0
31
1
1
Order By: Relevance
“…For example, internal mobility and circular migration for sex work (e.g., between districts, travel to religious festivals) [40,41,43] and venue instability (e.g., mobility between different sex work venues) [27,42,58] have been linked to elevated HIV prevalence in a number of settings whereas migration to higher-income settings has been shown to be protective against HIV infection [59]. Variation in HIV transmission risks among migrant sex workers have been increasingly shown to be a product of intersecting macrostructural factors (e.g., political and economic instability and HIV burden of place of origin, immigration policies, language, and cultural contexts of host-setting) and the work environment features they engender (e.g., economic opportunities and social mobility, violence and policing, health access) [40,41,60,61].…”
Section: Epidemiology Of Structural Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, internal mobility and circular migration for sex work (e.g., between districts, travel to religious festivals) [40,41,43] and venue instability (e.g., mobility between different sex work venues) [27,42,58] have been linked to elevated HIV prevalence in a number of settings whereas migration to higher-income settings has been shown to be protective against HIV infection [59]. Variation in HIV transmission risks among migrant sex workers have been increasingly shown to be a product of intersecting macrostructural factors (e.g., political and economic instability and HIV burden of place of origin, immigration policies, language, and cultural contexts of host-setting) and the work environment features they engender (e.g., economic opportunities and social mobility, violence and policing, health access) [40,41,60,61].…”
Section: Epidemiology Of Structural Determinantsmentioning
confidence: 99%
“…A large number of studies have examined types of venues and their relationships with HIV risks or protections among FSWs, underscoring the heterogeneous and context- specific nature of work environments [39,42,46,47,50,54,58,65,67,6976]. Only a handful of studies have started to disentangle the complexities and unique and iterative effects of policy, physical, social, and economic features of work environments that are specific to local sex industries and shape HIV prevention, treatment, and care [54,77,78,79,80,81].…”
Section: Epidemiology Of Structural Determinantsmentioning
confidence: 99%
“…Most publications were cross-sectional (n = 25), four were longitudinal [4952], and one was a case study [53]. There were 23 quantitative studies and seven qualitative studies [5359].…”
Section: Resultsmentioning
confidence: 99%
“…There was also a direct impact of economic pressure on general HIV-related sexual risk and on inconsistent condom use in the past 6 months [51]. One study suggested a non-significant correlation between self-rated financial situation and consistent condom use5 [52]. …”
Section: Condom Usementioning
confidence: 99%
“…Eleven of these interventions occurred in the U.S. with sub-populations of women affected by substance use (racial/ethnic minority, 21, 22 incarcerated, 23, 24 and homeless 25 women), engaged in active substance use, 2632 or living with HIV. 33 The others targeted substance-using female sex workers in Mexico 34, 35 and South Africa, 36 high-risk heterosexual women in the U.S. Virgin Islands 37 and Puerto Rico, 38 and pregnant IDU accessing methadone in Australia. 39 …”
Section: Resultsmentioning
confidence: 99%